The Travels of Ibn Batuta with Notes, illustrative of the history, geography, botany, antiquities, Etc. occurring throughout the work - Lee, Samuel; Lee, Samuel (Cambridge library collection, 2012)
An 1829 English edition of the work of the Arab traveller Ibn Battuta (1304-68/9), whose journeys may have reached as far as China and Zanzibar. There is doubt as to whether Ibn Battuta actually saw everything he described, but this account gives a fascinating world-view from the medieval period